PERBANDINGAN MARKER INFLAMASI ANTARA SINDROMA KORONER AKUT DAN NON SINDROMA KORONER AKUT Myeloperoxidase dan High Sensitive C-Reactive Protein sebagai marker inflamasi pada dislipidemia - , SIENNY LINAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The number of dyslipidemia patient has rapidly increased. Dyslipidemia is a major risk factor of coronary heart disease. Chronic inflamation and endothel disfunction is factor that act in inisiation and progressiveness of coronary disease. Atherosclerosis process in coronary artery is early process from Acute Coronary Syndrome (ACS). Atherosclerosis is chronic inflammation disease that characteristiced with lipid infiltration dan inflamation cell, such as macrophage derived monocyte and T limphocyte to artery wall. Myeloperoxidase (MPO) is hemoprotein in azurophilic granule, which released to extracelluler liquid and circulation during inflamation process. The aims of this study is to analyze comparation between MPO (Myeloperoxidase) and hs CRP (High Sensitive C-Reactive Protein) level as inflammation marker of dyslipidemia non ACS and dyslipidemia ACS patients. This study use a cross sectional design. The subject of this study is dyslipidemia non ACS patient who came to Internal Medicine Departement and dyslipidemia ACS patient who came to emergency care unit and analyze blood sample in Laboratory of Clinical Pathology at dr. Moewardi Hospital Surakarta. To analyze this result we use independent t-test/Mann withney test and Spearman/Pearson (r) correlation using computer programme, with degree of level significancy p < 0,05, and confidence interval 95%. Myeloperoxidase is early marker of inflamation process which happenned in dyslipidemia non ACS and dyslipidemia ACS patients.